Kritik Sosial dalam Puisi Negeri di Tepi Jurang Karya Fadli Zon dan Ayyuha al-Nas Karya Tamim Barghouti - Al-amien, Habib (Universitas Al Azhar Indonesia, 2024)
This research focused on the patterns of social criticism found in the poems of Fadli Zon and Tamim, both of whom are political experts, through a comparison of their similarities and differences. The method used in this research is descriptive qualitative research. The data collection method employed is the reading and note-taking method. The data sources are Fadli Zon's poem titled